2020
DOI: 10.1177/0894439320907067
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Forced Answering and Reactance on Answering Behavior in Online Surveys

Abstract: Forced answering (FA) is a frequent answer format in online surveys that forces respondents to answer each question in order to proceed through the questionnaire. The underlying rationale is to decrease the amount of missing data. Despite its popularity, empirical research on the impact of FA on respondents’ answering behavior is scarce and has generated mixed findings. In fact, some quasi-experimental studies showed that FA has detrimental consequences such as increased survey dropout rates and faking behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 77 publications
(105 reference statements)
3
27
0
Order By: Relevance
“…Thus, we suggest that future research employs alternatives to FA. For instance, using “soft reminders” alongside offering a “Prefer not to answer” (Sischka et al 2020 ) or “Not wish to disclose” as an additional option whilst responding to the questionnaire items could minimise missing data without elevating the risk of FA bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we suggest that future research employs alternatives to FA. For instance, using “soft reminders” alongside offering a “Prefer not to answer” (Sischka et al 2020 ) or “Not wish to disclose” as an additional option whilst responding to the questionnaire items could minimise missing data without elevating the risk of FA bias.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the procedure aimed for the avoidance of missing data rather than “forcing” the participants to respond. Also, our survey did not tap into personally sensitive questions (Sischka et al 2020 ). Therefore, we argue that the low dropout rate (Stieger et al 2007 ) represented by the high response rate of our survey (70%) indicates that slight bias was associated with the force answering (FA) in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1,609 participants (73.8%) took part and were compensated each with US $1.20. 4 No forced answering design was implemented as this has been found to be detrimental in terms of data quality (Sischka et al, 2020b ). We filtered out workers who indicated that their employment status had changed between prescreening and the actual survey (e.g., from employment to unemployment; 0.9%; n = 15).…”
Section: Methodsmentioning
confidence: 99%
“…Respondents' survey attitude and motivation to participate strongly correlate with the saliency of a survey (Groves et al 2000;Blom et al 2015;Sischka et al 2020). Survey managers are therefore interested in designing surveys that increase respondents' willingness to participate.…”
Section: Dealing With the Second Recruitment Challenge: Participation In Online Panelsmentioning
confidence: 99%